Comparing transcranial direct current stimulation and transcranial random noise stimulation over left dorsolateral prefrontal cortex and left inferior frontal gyrus: Effects on divergent and convergent thinking - Peña, Javier; Sampedro, Agurne; Balboa-Bandeira, Yolanda; Ibarretxe-Bilbao, Naroa; Zubiaurre-Elorza, Leire; García-Guerrero, M. Acebo; Ojeda, Natalia (Frontiers in Human Neuroscience, 2022)
The essential role of creativity has been highlighted in several human knowledge areas. Regarding the neural underpinnings of creativity, there is evidence about the role of left dorsolateral prefrontal cortex (DLPFC) and left inferior frontal gyrus (IFG) on divergent thinking (DT) and convergent thinking (CT). Transcranial stimulation studies suggest that the left DLPFC is associated with both DT and CT, whereas left IFG is more related to DT. However, none of the previous studies have targeted both hubs simultaneously and compared transcranial direct current stimulation (tDCS) and random noise stimulation (tRNS). Additionally, given the relationship between cognitive flexibility and creativity, we included it in order to check if the improvement in creativity may be mediated by cognitive flexibility. In this double-blind, between-subjects study, 66 healthy participants were randomly assigned to one of three groups (N=22) that received a transcranial direct current stimulation (tDCS), transcranial random noise stimulation (tRNS) or sham for 20 minutes. The tDCS group received 1,5mA with the anode over the left DLPFC and cathode over the left IFG. Locations in tRNS group were the same and they received 1,5mA of high frequency tRNS (100–500Hz). Divergent thinking was assessed before (baseline) and during stimulation with Unusual Uses (UU) and Picture Completion (PC) subtests from Torrance Creative thinking Test, whereas convergent thinking was evaluated with the Remote Association test (RAT). Stroop test was included to assess cognitive flexibility. ANCOVA results of performance under stimulation (controlling for baseline performance) showed that there were significant differences in PC (F=3.35, p=0.042, n_p^2 =0.10) but not in UU (F=0.61, p=0.546) and RAT (F=2.65, p=0.079) scores. Post-hoc analyses showed that tRNS group had significantly higher scores compared to sham (p=0.004) in PC. More specifically, tRNS showed higher performance in fluency (p=0.012) and originality (p=0.021) dimensions of PC compared to sham. Regarding cognitive flexibility, we did not find any significant effect of any of the stimulation groups (F=0.34, p=0.711). Therefore, no further mediation analyses were performed. Finally, the group that received tDCS reported more adverse effects than sham group (F=3.46, p=0.035). Altogether, these results suggest that tRNS may have some advantages over tDCS in DT.